2007
DOI: 10.1128/jvi.00321-07
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Adaptation to Untranslated Region-Mediated Enterovirus Growth Deficits by Mutations in the Nonstructural Proteins 3AB and 3CD

Abstract: Both untranslated regions (UTRs) of plus-strand RNA virus genomes jointly control translation and replication of viral genomes. In the case of the Enterovirus genus of the Picornaviridae family, the 5UTR consists of a cloverleaf-like terminus preceding the internal ribosomal entry site (IRES) and the 3 terminus is composed of a structured 3UTR and poly ( Enterovirus (EV) plus-strand RNA genome translation and replication are controlled by cis-acting sequence elements mapping to the open reading frame and both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…Chimeric polioviruses possessing heterologous 5Ј UTRs from coxsackievirus or rhinovirus have exhibited growth deficiencies in cell culture and attenuated neuropathogenesis in poliomyelitis mouse models though they share ϳ70% nucleotide identity across the 5Ј UTRs (13,18). Other investigators have observed complementary mutations in 3A/3AB and 3C/3CD that alleviate cell-type-specific growth defects in enteroviruses with incompatible UTRs; although the mutations were confined to the 3A and 3C regions, homogenous mutations were not identified at defined sites (9). Future site-directed mutagenesis studies using EV109 could elucidate the selected coding region mutations needed to maintain UTR-viral protein interactions within the context of a natural recombination event.…”
Section: Discussionmentioning
confidence: 99%
“…Chimeric polioviruses possessing heterologous 5Ј UTRs from coxsackievirus or rhinovirus have exhibited growth deficiencies in cell culture and attenuated neuropathogenesis in poliomyelitis mouse models though they share ϳ70% nucleotide identity across the 5Ј UTRs (13,18). Other investigators have observed complementary mutations in 3A/3AB and 3C/3CD that alleviate cell-type-specific growth defects in enteroviruses with incompatible UTRs; although the mutations were confined to the 3A and 3C regions, homogenous mutations were not identified at defined sites (9). Future site-directed mutagenesis studies using EV109 could elucidate the selected coding region mutations needed to maintain UTR-viral protein interactions within the context of a natural recombination event.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the growth curve experiments, the cultures were rinsed with DMEM (Invitrogen). The experimental setup was a standard one-step growth curve (13). Briefly, cells in a control well were treated with trypsin and counted using a hemocytometer to determine the amount of virus needed to achieve a multiplicity of infection (MOI) of 10.…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing of viral genomes followed earlier published procedures (17 (Table 1) were used to generate overlapping PCR products covering Ͼ99% of the viral genome (we were unable to determine the sequence of the ϳ30 5Ј-most and 3Ј-most nucleotides of the viral RNA). A variable combination of primers 6 to 39 (Table 1) was used for sequencing of the RT-PCR products.…”
Section: Vol 85 2011 Mouse Respiratory Tract-adapted Coxsackievirusmentioning
confidence: 99%
“…Virus obtained after the final passage was used for plaque purification by standard methods. One-step growth curves were established as previously described (17). To analyze hICAM-1 signaling upon CAV21 binding, HeLa H1 cells were serum starved for 48 h and infected at an MOI of 10.…”
Section: Vol 85 2011 Mouse Respiratory Tract-adapted Coxsackievirusmentioning
confidence: 99%
See 1 more Smart Citation